The Basic Characteristics of Skills and Organizational Capabilities in the Indian Software Industry - Ted Tschang (Asian Development Bank Institute (ADBI), 2001)
The Indian software industry has come to be regarded by developing countries the world over as amodel for how they can leapfrog stages of industrial development. Its success is a story of hard workand fortuitous circumstances: the hard work being the building of a world class pool of computerprogramming talent; the fortuitousness being the increasing demand for personnel in the USinformation industry. This paper examines some of the factors in that success by focusing on the basiccharacteristics of India's skills and organizations. The limitations of the current trajectory, along withscenarios for the evolution of the industry, are also examined.
hdl:11540/4118
Keywords: 330